Health promotion to enhance the active role of Pabelan Village health cadres in preventing noncommunicable disease - Arif Widodo; Ana Safira Salsabila; Farras Kens Daryngga (Community Empowerment, 2023)
Noncommunicable disease (NCDs) is a disease that cannot be diagnosed with certainty if the patient has no symptoms and complaints, where most of the deaths worldwide are caused by NCDs. Health promotion should be given to cadres in order to increase the knowledge and attitudes of Pabelan Village health professionals towards the prevention of NCDs. This community service aims to increase the knowledge and attitudes of health cadres in preventing NCDs. Program carried out in the form of health promotion and blood pressure check skills education. The results of the program showed an increase in the knowledge and attitudes of cadres after being given health promotion, and an increase in skills related to checking blood pressure.